Effect of transglutaminase treatment on the physicochemical properties and structural characteristics of soy protein isolate/konjac glucomannan complex - Wang, Ya; Lei, Ailin; Zhan, Ziyi; Sun, Xiaohua; Zhang, Fusheng (Food chemistry, 2025)
In this study, the effects of transglutaminase on the structural and physicochemical properties of soy protein isolate/konjac glucomannan complex were investigated. Additionally, the complex was treated with different transglutaminase additions, cross-linking temperatures, and cross-linking pH and compared with a control without transglutaminase to elucidate the effect of transglutaminase on the internal interactions within the complex. The results demonstrated that transglutaminase treatment significantly enhanced the water-holding and oil-binding capacities by 34.62 % and 49.28 %, respectively, along with the emulsifying properties. Furthermore, transglutaminase treatment significantly enhanced the UV absorption intensity by 36.89 % and strengthened the intermolecular interactions. The relative crystallinity and ΔH were elevated by 15.08 % and 34.39 %, respectively, which significantly enhanced the thermal stability of the complex. Overall, the transglutaminase-treated complex displayed improved physicochemical properties, with a more organized, uniform, and denser internal structure. These findings offer valuable insights into developing novel plant-based fat mimetics. [Display omitted] •Transglutaminase enhanced the cross-linking interaction of the complex.•Transglutaminase improved the emulsifying and rheological properties of the complex.•The transglutaminase-treated complex had enhanced thermal and structural stability.•Transglutaminase promotes denser structure by enhancing disulfide and hydrogen bond.•The findings offer insights into developing novel plant-based fat mimetics.